2020
DOI: 10.5751/es-11590-250227
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing resilient forest biodiversity: nest webs as complex adaptive systems

Abstract: Forests are complex adaptive systems in which properties at higher levels emerge from localized networks of many entities interacting at lower levels, allowing the development of multiple ecological pathways and processes. Cavity-nesters exist within networks known as "nest webs" that link trees, excavators, e.g. woodpeckers, and nonexcavators (many songbirds, ducks, raptors, and other organisms) at the community level. We use the idea of panarchy (interacting adaptive cycles at multiple spatio-temporal scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…We found that tree density was much higher in secondary than in old-growth forest stands and the density of dead trees was comparable for both forest types. However, the density of cavity-bearing trees was much higher in old-growth forests, indicating the importance of these structurally complex stands as habitat for cavity-using wildlife in temperate ecosystems (Zenner 2004;Bunnell 2013;Caviedes & Ibarra 2017;Ibarra et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that tree density was much higher in secondary than in old-growth forest stands and the density of dead trees was comparable for both forest types. However, the density of cavity-bearing trees was much higher in old-growth forests, indicating the importance of these structurally complex stands as habitat for cavity-using wildlife in temperate ecosystems (Zenner 2004;Bunnell 2013;Caviedes & Ibarra 2017;Ibarra et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the density of cavity‐bearing trees was much higher in old‐growth forests, indicating the importance of these structurally complex stands as habitat for cavity‐using wildlife in temperate ecosystems (Zenner 2004; Bunnell 2013; Caviedes & Ibarra 2017; Ibarra et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This result associates with the observed steep relationship between beetle species richness and functional richness, in relation to a random expectation, that started to saturate with relatively high beetle richness 48,49 . This nding suggest that homegardens with high functionally redundancy will be more resilient to shifts in social-ecological lters [50][51][52] .…”
Section: Discussionmentioning
confidence: 83%
“…Structurally complex homegardens will not only increase the functional niche space lled by species in beetle communities and enhance bene cial organisms, such as pest-control predators, pollinators, and seed dispersers 13 , they will also be more important carbon sinks than those that are structurally simpli ed and lack trees 73 . In a complexity science context, this result suggests that these small-scale systems have a social-ecological memory in which older and structurally complex homegardens act as long-lived system entities whose presence continues to in uence compositional, structural, and functional states of the system over time 51 .…”
Section: Social-ecological Lters and Beetle Communitiesmentioning
confidence: 98%
“…In the last 50 years, a paradigm shift has occurred in science with the emergence of the paradigm of complexity [9], and so-called complexity science, in which the study object evolved from separate components to a focus on the whole [10][11][12]. This shift has meant that many researchers no longer focus on linear and deterministic processes but rather on self-organized networks of interactive actors that give rise to complex systems [13][14][15]. This approach tried to overcome the limitations of mainstream scientific knowledge, which posits the objectivity of scientific truths, acknowledging the need for a comprehensive and contextual approach dealing with uncertainties [8,10,16,17].…”
Section: Introductionmentioning
confidence: 99%